Improving student achievement with smart sheets Media in islamic cultural history lesson at the Elevent grade students of mtsn tarusan - Sasmini Sasmini (Fakultas Sastra Universitas Ekasakti, 2017)
To be able to learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to